2016
DOI: 10.1007/s12250-016-3754-0
|View full text |Cite
|
Sign up to set email alerts
|

Multipotent mesenchymal stromal cells are fully permissive for human cytomegalovirus infection

Abstract: Congenital human cytomegalovirus (HCMV) infection is a leading infectious cause of birth defects. Previous studies have reported birth defects with multiple organ maldevelopment in congenital HCMV-infected neonates. Multipotent mesenchymal stromal cells (MSCs) are a group of stem/progenitor cells that are multi-potent and can self-renew, and they play a vital role in multi-organ formation. Whether MSCs are susceptible to HCMV infection is unclear. In this study, MSCs were isolated from Wharton's jelly of the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
1
3
0
1
Order By: Relevance
“…The susceptibility and permissibility of prASCs to HCMV was not known before our experiments, but is consistent with reported productive infection of MSC derived from bone marrow [20], umbilical cord Wharton’s jelly [49], placenta [50] and MSC from subcutaneous adipose tissue [51] The perivascular niche was described as a relevant MSC origin across the human organs [1]. In addition perivascular stromal cells host HCMV and are a likely long term reservoir [52].…”
Section: Discussionsupporting
confidence: 91%
“…The susceptibility and permissibility of prASCs to HCMV was not known before our experiments, but is consistent with reported productive infection of MSC derived from bone marrow [20], umbilical cord Wharton’s jelly [49], placenta [50] and MSC from subcutaneous adipose tissue [51] The perivascular niche was described as a relevant MSC origin across the human organs [1]. In addition perivascular stromal cells host HCMV and are a likely long term reservoir [52].…”
Section: Discussionsupporting
confidence: 91%
“…Qiao et al [ 204 ]and Soland et al [ 205 ] reported that human MSCs were fully permissive to human cytomegalovirus infection, and the highest infection rate was observed in lung perivascular MSCs, suggesting that MSCs in different organs might act as a viral reservoir in humans. Further, Meisel et al [ 206 ] found that MSCs infected with CMV lose their immunosuppressive and antimicrobial properties, and Sundin et al [ 207 ] found that parvovirus B19 persisted in BM-MSCs even after several years of infection.…”
Section: Challenges In Utilizing Mscsmentioning
confidence: 99%
“…MSC surface receptor expression and viral tropism may partially explain MSC susceptibility to viral infection. MSCs are highly permissive to infection by many genera of Herpesviruses, including Herpes Simplex-1 (HSV-1), Varicella Zoster virus (VZV) and Cytomegalovirus (CMV) [ 27 ]. HSV-1 can infect MSCs through the heparan sulfate receptor [ 28 ].…”
Section: Viral Infection Of Mscs Potential Outcomes and Safetymentioning
confidence: 99%